THE RELATION BETWEEN DURATION OF FIXED ORTHODONTIC TREATMENT AND ORAL HYGIENE STATUS AMONG STUDENTS OF FACULTY OF DENTISTRY UNIVERSITAS MUSLIM INDONESIA 2017 - Yustisia Puspitasari; Aulia Aita Aswar; Ilmianti Ilmianti (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Fixed orthodontic treatment is now widely used in society, but people often do not realize the risks of using this appliance such as the rise of oral hygiene and caries problem. The design of this appliance is more difficult to clean than removable orthodontic appliance so it can cause a variety of oral disease if long-term fixed orthodontic treatment is required and the cleanliness of the teeth and mouth is not maintained. According to RISKESDAS 2013, Ministry of Health of Indonesia reported that the prevalence of oral disease reached 25.9%. The results showed an increase in the prevalence of oral disesase compared to RISKESDAS 2007 results. Objective : to investigate the relation between duration of fixed orthodontic treatment and oral hygiene status among the students of Faculty of Dentistry Universitas Muslim Indonesia 2017. Method : The study was conducted as an analytic observational study with cross-sectional study design. Samples of this research were students of Faculty of Dentistry, Universitas Muslim Indonesia, Makassar, Indonesia. Oral hygiene status were analyzed using Attin Index. The result was statiscally analyzed with Chi-Square test. Results : The p value of this research was less than 0.05, therefore the results of this research are statistically significant. Conclusion : Hypothesis was accepted and showed that there was a significant relation between the duration of fixed orthodontic treatment and oral hygiene status among the students of Faculty of Dentistry Universitas Muslim Indonesia 2017.